New observational and experimental evidence for the recharge mechanism of the lake group in the Alxa Desert, north-central China. (January 2016) - Dong, Chunyu; Wang, Nai'ang; Chen, Jiansheng; Li, Zhuolun; Chen, Hongbao; Chen, Li; Ma, Ning
Abstract: The Alxa Desert in north-central China has a unique landscape that contains hundreds of lakes and the highest sand dunes in the world. To date, however, the explanation of the water source in this desert is still controversial. In this paper, continuous hydrometeorological observations, including precipitation, evaporation, water level and temperature, in the interior of the Alxa Desert are presented and the water balance of a typical desert lake is calculated. The moisture, Cl − concentration, δ 2 H and δ 18 O of several sand profiles, the hydrogeochemical characteristics of some lakes and groundwater, and the elemental composition of some travertine samples are analyzed to investigate the rainfall percolation and groundwater recharge. The results showed that local precipitation is not the major replenishment source of the lakes and groundwater in the Alxa Desert. It is supposed that the groundwater from deep strata in the adjacent fracture zone might recharge the desert lake group from the southeast along an altitudinal gradient. Highlights: Hydrometeorological observations in the Alxa Desert were presented. Local precipitation has no significant contribution to the desert groundwater. Deep groundwater might be the primary recharge source of the lake groups.